Pharmacokinetics of vancomycin following intracameral bolus injection in patients undergoing phacoemulsification cataract surgery. Issue 10 (27th March 2007) - Murphy, Conor C; Nicholson, Steven; Quah, Say Aun; Batterbury, Mark; Neal, Timothy; Kaye, Stephen B
Abstract : Aim: To determine the elimination kinetics of intracameral vancomycin administered as a bolus injection at the end of phacoemulsification cataract surgery. Methods: Vancomycin 1 mg/0.1 ml saline solution was administered to 19 patients by intracameral bolus injection at the end of routine cataract surgery. The aqueous concentration of vancomycin was determined in nine patients 1 minute after administration and in 10 patients 18–24 hours postoperatively. Aqueous samples were obtained by inserting a Rycroft cannula into the anterior chamber via the side port incision. Fluorescence polarisation immunoassay was used to calculate the aqueous vancomycin concentration. Results: The median (interquartile range) vancomycin concentration was 5458 (4756–6389) mg/l at 1 minute and 40.6 (25.9–47.1) mg/l 18 to 24 hours (median 19 hours) postoperatively. The vancomycin concentration exceeded the minimum inhibitory concentration (MIC) of endophthalmitis-causing gram-positive bacteria by a factor of 4 for up to 26 hours postoperatively. No adverse event or reaction was noted. Conclusion: Following bolus intracameral injection at the end of cataract surgery the concentration of vancomycin in the anterior chamber vastly exceeds its MIC for at least 24 hours but is predicted to fall below the MIC after 33 hours.